Antecedents of customer loyalty towards private commercial banks in Bangladesh / Md Wasiul Karim and Mohammad Abdul Matin Chowdhury - Karim, Md Wasiul; Chowdhury, Mohammad Abdul Matin (Universiti Teknologi MARA, 2021)
Banks are an essential part of every business and economy. As the number of banks are increasing to provide valuable services to clients, customers with numerous expectations regarding new products and services are assisting to build loyalty. In this regard, the current study intended to examine the antecedents of customer loyalty towards private commercial banks in Bangladesh. The Stimulus-Organism-Response (S-O-R) was employed. A total of 257 data was received from the respondents who have been experiencing banking services. The data was analyzed by deploying the SPSS and AMOS version 21.0. The result indicated that, satisfaction has a significant influence on customer loyalty. The findings further reveal that perceived value has significant impact on both satisfaction and customer loyalty and it was also noted that satisfaction was partially mediated by perceived value and customer loyalty. On the other hand, staff competency was found to be insignificant in determining the relationship with customer loyalty but significant with customer satisfaction. The findings from this study will enhance private commercial bank service providers involved in the operations to understand the best approach that can be taken to serve customers better.